The ANALYSIS OF CURRENT FED ISOLATED FULL BRIDGE DCDC WITH VOLTAGE MULTIPLIE (International Journal of Engineering Management Science, 2022)
Active clamp concept introduced on the primary side of isolation transformer to reduce the turn-off voltage spikes of full bridge active devices. Innate soft-switching with elongated range can be achieved in the recommended converter by using the parasitic capacitance of MOSFET switches and leakage inductance of the high frequency transformer. Zero Voltage Switching(ZVS) is achieved for all the primary devices which allow greater switching frequency operation and improvement in over-all efficiency of the converter for utility interface. Cost, size and weight of the converter minimizes for the higher switching operation of the converter. Half-wave Cockcroft-Walton Voltage Multiplier (H-W C-W VM) having minimum number of multiplying stages is used on the secondary side of the designed converter in order to get the required DC-link voltage for three phase utility grid connection. The converter’s switching frequency is maintained at 100 KHz. This paper is organized as introduction, steady state operation, simulation results with two different cases i.e. full load and half load conditions and finally, test result validation of a 250 Watt experimental setup with the proposed converter. High-boost dc-ac inverters are used in solar photovoltaic (PV), fuel cell, wind energy, and uninterruptible power supply systems. High step-up and step-down capabilities and shoot-through immunity are some of the desired properties of an inverter for a reliable, versatile, and low-distortion ac inversion. The recently developed Z-source inverter (ZSI) possesses these qualities. However, the realization of ZSI comes at a cost of higher passive component count as it needs two sets of passive filters. A switched boost inverter (SBI) has similar properties as ZSI, and it has one L-C pair less compared to ZSI, but its gain is less than ZSI. This paper proposes the current-fed switched inverter (CFSI) which combines the high-gain property of ZSI and low passive component count of SBI. The proposed inverter uses only one L-C filter and three switches apart from the inverter structure.